2001
DOI: 10.1007/s002040100245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local blood flow on the percutaneous absorption of the organophosphorus compound malathion: a microdialysis study in man

Abstract: Malathion [O,O-dimethyl-S-(1,2-dicarbethoxyethyl)phosphorodithioate] is an organophosphorus insecticide widely used in veterinary medicine and in humans for the treatment of lice. In this study, the rate of the percutaneous absorption of malathion has been measured in human skin, in vivo, using microdialysis. Malathion was detected in tissue dialysate within 30 min of its topical application to the skin of the volar surface of the forearm of healthy volunteers. The concentration of malathion in dialysate incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 0 publications
4
35
1
Order By: Relevance
“…However, there is increasing awareness that recovery of solute from the tissue space by dialysis is subject to many variables, including mass transport processes between the blood and tissues (Bungay et al, 1990;Singh and Roberts, 1993;Borg et al, 1999;Sun et al, 2001). Indeed, recent studies in our own laboratory in which we used microdialysis to assess the distribution and clearance of an organophosphorus compound in human skin in vivo showed that local vasodilatation, caused by the compound itself, had a significant impact on dialysis recovery from the tissue space and, by implication, on the local and systemic distribution of the compound (Boutsiouki et al, 2001). We attempted to investigate this further in the present study by focusing on the influence of local blood flow on dialysis probe extraction through the correlation of recovery of sodium fluorescein with altered blood flow in human skin in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is increasing awareness that recovery of solute from the tissue space by dialysis is subject to many variables, including mass transport processes between the blood and tissues (Bungay et al, 1990;Singh and Roberts, 1993;Borg et al, 1999;Sun et al, 2001). Indeed, recent studies in our own laboratory in which we used microdialysis to assess the distribution and clearance of an organophosphorus compound in human skin in vivo showed that local vasodilatation, caused by the compound itself, had a significant impact on dialysis recovery from the tissue space and, by implication, on the local and systemic distribution of the compound (Boutsiouki et al, 2001). We attempted to investigate this further in the present study by focusing on the influence of local blood flow on dialysis probe extraction through the correlation of recovery of sodium fluorescein with altered blood flow in human skin in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…NA perfusion was maintained throughout the experiment. GTN, which has been shown to cause local vascular damage leading to hemostasis if delivered by microdialysis (Boutsiouki et al, 2001), was delivered to a second site using a patch (Transderm-Nitro 5; Novartis Pharmaceuticals UK Ltd., Surrey, UK) applied for 30 min before the start of fluorescein-probe perfusion. Perfusion of one of the probes beneath the GTN patch (retrieval probe) with PBS was initiated on application of the patch 30 min before the start of perfusion of the second (delivery) probe with the fluoresceincontaining perfusate.…”
Section: Methodsmentioning
confidence: 99%
“…The skin concentration of a topically applied drug will increase if the blood flow is diminished, whereas an increased blood flow enhances the uptake and subsequent systemic distribution and elimination of the drug from the skin [39] . Experimental studies which induce vasoconstriction or vasodilatation have demonstrated that the BA of topically as well as systemically applied test substances is highly influenced by changes in the microcirculation of the skin [69,97,128,129] -an influence much stronger than the influence of variations in probe depth.…”
Section: Microcirculationmentioning
confidence: 99%
“…Menthol is included in Deep Relief as a second active moiety, because it possesses pharmacological properties which are not only directly relevant to pain relief, per se, but can also have a profound effect on the pharmacodynamics of co-permeating species in vivo. The importance of modulating effects on the local microvasculature on skin penetration has been described by several authors [22][23][24] . In addition to its well-known cooling effect, menthol can stimulate skin nociceptors and initiate an axon refl ex with subsequent release of vasodilator peptides [25] , and an increase in skin temperature and underlying muscle temperature has been shown after topical application of a mixture of eucalyptus oil and menthol [26] .…”
Section: Resultsmentioning
confidence: 99%